2017
DOI: 10.25251/skin.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Body Contouring: Literature Review and Summary of Objective Data

Abstract: Capsule Summary:• Noninvasive body contouring devices vary by efficacy, treatment schedule and safety profile.• This review compares body contouring modalities, allowing for quick comparison between modalities.• This review enables the selection of a body contouring modality that best suits each specific patient's goals, availability and aversion to risk. Background: There is increasing demand for noninvasive body contouring but objective data is difficult to compare between modalities. Currently, the most acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The popularity of non‐invasive body shaping procedures has been growing rapidly—the number of procedures performed in the US more than doubled between 2012 and 2016 . Cryolipolysis, radiofrequency, low level laser therapy and focused ultrasound are most widely used for treating patients’ fat bulges, and their efficacy has been demonstrated in multiple previous studies. Similar to every aesthetic procedure, these technologies have also certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of non‐invasive body shaping procedures has been growing rapidly—the number of procedures performed in the US more than doubled between 2012 and 2016 . Cryolipolysis, radiofrequency, low level laser therapy and focused ultrasound are most widely used for treating patients’ fat bulges, and their efficacy has been demonstrated in multiple previous studies. Similar to every aesthetic procedure, these technologies have also certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Until then, fat apoptosis in noninvasive body shaping had always been associated with direct exposure to thermal stress, such as cooling with cryolipolysis or heating with radiofrequency. 27 The study by Weiss et al 7 proposed a theory that apoptosis may be related to the high energy demand of the contracting muscles, and since glycogen is quickly depleted, a fat breakdown into free fatty acids (FFAs) and glycerol is initiated. However, the release of FFAs is exaggerated to such a degree that the fat cells are unable to dispose of the FFAs into the bloodstream quickly enough and the concentration of FFAs inside the cells becomes toxic.…”
Section: What Is Hifem Technology and How It Work?mentioning
confidence: 99%
“…Initial trials showed that patients lost a significant amount of fat in the subcutaneous layer after the treatment, and a consequent histological study performed by Weiss et al 7 showed that HIFEM treatment induces fat cell apoptosis. Until then, fat apoptosis in noninvasive body shaping had always been associated with direct exposure to thermal stress, such as cooling with cryolipolysis or heating with radiofrequency 27 . The study by Weiss et al 7 proposed a theory that apoptosis may be related to the high energy demand of the contracting muscles, and since glycogen is quickly depleted, a fat breakdown into free fatty acids (FFAs) and glycerol is initiated.…”
Section: What Is Hifem Technology and How It Work?mentioning
confidence: 99%
“…[5][6][7] RF-driven body contouring devices are very popular but require many treatment sessions and their effectiveness is limited. 8 The safety and efficacy of a 1060-nm diode laser reduction on fat layer thickness of the flanks and abdomen has been recently reported [9][10][11][12] yet these publications are quite sparse.…”
Section: Introductionmentioning
confidence: 99%
“…However, nearly all patients develop erythema, edema, dysethesia and discomfort at the treatment site, and pain is commonly reported as well 5–7 . RF‐driven body contouring devices are very popular but require many treatment sessions and their effectiveness is limited 8 . The safety and efficacy of a 1060‐nm diode laser reduction on fat layer thickness of the flanks and abdomen has been recently reported 9–12 yet these publications are quite sparse.…”
Section: Introductionmentioning
confidence: 99%